Gross histopathological features and treatment outcomes of ameloblastoma at Khartoum teaching dental hospital: A retrospective cross-sectional study - Saba Eltayeb Mohammed Ahmed (BMC Cancer, 2025)
Abstract Aim The aim of this study is to interrogate the gross histopathological patterns, correlation between histological type with tumor location, treatment, and complications of patients with ameloblastomas seen at Khartoum Teaching Dental Hospital. Method This was a cross-sectional retrospective laboratory-based study using 390 patients identified histologically with ameloblastoma between the years 2010–2017. Information regarding age, gender, histopathologic type, anatomical site, tumour size, clinical and radiographic data as well as biological features of the types of ameloblastoma was obtained from laboratory demand outlines. Categorical and continuous variables were summarized in percentage and mean ± standard deviation, respectively. Continuous and categorical variables were summarized using mean ± standard deviation (SD) and percentages, respectively. Sociodemographic characteristics and healthcare-related variables were compared using the chi-square test, while economic status was analyzed using Duncan’s multiple range test. Results A total of 390 patients of ameloblastoma were included with a mean patient age of 30.74 ± 5.21 years (range: 9–68 years), male to female ratio of patients was 1.3:1. Maximum of approximately 68.46% (n = 267) patients presented with a painless swelling involving the mandible. Follicular pattern was the most predominant histopathological pattern 44.87% (n = 175) followed by plexiform pattern, accounted for 32.82% (n = 128) but in the recurrent cases, there was a relatively higher number of plexiform patterns 11.54% (n = 45), unlike other histopathological patterns. Patients that had recurrence, only 1.28% (n = 5) were treated by radical surgery compared to 23.32% (n = 91) who underwent conservative surgery. Conclusion This investigation reports a reasonably significant rate of recurrence in approximately a quarter 24.62% (n = 96) of the study patients. This is the largest histopathological study regarding ameloblastoma management from Sudan, and our results recommending radical surgery for the treatment of tumours.